Mitral valve prolapse as cause of terminal ventricular complex ischaemia: a clinical case - S. A. Chepurnenko; G. V. Shavkuta; A. D. Nasytko (Кубанский научный медицинский вестник, 2021)
Background. Mitral valve prolapse has common prevalence of 1% in population. Patients with mitral valve prolapse (MVP) continue to pose a major challenge in practical cardiology for its nonspecific manifestations, usually, palpitations and atypical chest pain. Several studies have demonstrated a high incidence of ventricular arrhythmias in individuals with MVP. MVP was observed in 2.3% of patients with sudden cardiac death. Comparing to the common population with sudden cardiac death, MVP patients belonged to a younger age group and less frequently had concomitant cardiovascular pathology.Clinical Case Description. Patient T. referred with complaints of transient constricting chest pain at rest and exercise, dyspnoea at exercise. A total duration of ST-T segment displacement episodes was 168 min, with painless episodes prevailing. Spiral computed angiography did not reveal calcinosis, soft coronary atherosclerotic plaques or abnormal arterial origins. Severe ventricular repolarisation abnormalities with sinusoidal T-U waves morphology in MVP are harbingers of sudden cardiac death, despite a normal QT interval duration. The T wave inversion in the lower lead and ventricular extrasystole also comprise the risk factors for sudden cardiac death in patients with MVP.Conclusion. Mitral valve prolapse caused an ischaemic ST-T segment depression in a young woman indicating a high risk of sudden cardiac death and need for immediate drug therapy. The Russian recommendations on treatment of connective tissue dysplasia and known literature suggest magnesium preparations as a preferred medication. Beta-blockers are effective in increased sympathetic nervous system reactivity or tone. Collagen synthesis stimulators, vitamins C, D, P, group B, preparations of magnesium, calcium, manganese, copper and antihypoxants are also recommended. Treatment with bisoprolol and magnesium orotate eliminated ischaemia and ventricular extrasystoles and improved the patient’s condition.